The proclamation ceremonies of European monarchs in the 21st century: informative frames in the Spanish general press - Muñoz Boda, María Soledad (Revista General de Información y Documentación, 2022)
The main objective of this research is to analyse the proclamation ceremonies of European monarchs during the 21st century in the Spanish general press from the framing perspective, in order to understand the frames of a news report by section and the frames with respect to protagonists, actants, actions, symbology and settings. On the methodological basis of textual and graphic content analysis, we selected a sample composed of 190 pieces belonging to the journalism genre, that were published on the date of the celebration and the three days before and after, extracted from the newspapers: El País, ABC and La Vanguardia. In the report referring to foreign monarchies, the predominant frame in each respective paper corresponds to the Society/People/Living and International sections, in similar percentages, while the proclamation of Felipe VI, in ABC and El País is included in the National/Spain section, and in La Vanguardia in the Politics section. As for the actants and actions, the proclaimed monarch accompanied by his family becomes the main image; waving, posing and gazing outwards. Likewise, his symbolic link with the national flags appears repeatedly. In the scenographic framework, undefined spaces stand out; there are hardly any religious scenes (except in Monaco) and among those identified, the following stand out: street, Parliament and the Royal Palace. In conclusion, ABC lends greater relevance only to the ceremonies of Spain, the Netherlands and Luxembourg, coinciding the three newspapers with homogeneous and predictable news coverage, which proposes a stereotypical image marked by the tradition of these events.
Keywords: Ceremony; Proclamation; Monarchs; Monarchies; Europe; Analysis; Framing; Frames; Press; Spain